UPGRADING REJECTED CRUST LEATHER INTO A BATTING GLOVE ARTICLE WITH A DIGITAL MATRIX EMBOSS MOTIF - Erlinda Rahma Damayanti; Nais Pinta Adetya; Ragil Yuliatmo (Politek ATK Yogyakarta Press, 2024)
The aim of the research is to upgrade goat crust leather which was declared rejected to be made into batting glove articles with digital matrix embossed motifs, so as to increase the quality and selling value of the leather. Rejected leather is leather that does not meet the specifications of the intended article, for example defects, thickness and area. The digital matrix motif has a 3D pattern, so apart from adding aesthetic value, the digital matrix application on batting gloves also increases user comfort. The raw materials used were 4 pieces of crust reject leather which had wrinkles, ticks, fleas and coarse grain defects. Repairs were carried out using 2 methods, namely 3 skins using method A (re-process retanning, finishing, re-fatliquoring) and 1 skin using method B (finishing, re-fatliquoring). Testing is carried out physically. The results of physical testing showed that skin using method B was better in the elongation test (52.3%>49.5%) and softness (6.1mm>5.4mm). The results of the skin color fastness test using method A have better scores, namely 4/5 for dry paint rubbing resistance (staining and change in color) and 3/4 (staining and change in color) for wet paint rubbing resistance.